MANAJEMEN KEPALA SEKOLAH TERHADAP KINERJA GURU - Evi Ekawati (UNISAN JURNAL, 2024)
This exploration means to portray the Vital’s Authority in Further developing Educator Execution at SDN 1 Penengahan as well as the supporting and repressing elements for Head Administration in Further developing Instructor Execution at SDN 1 Penengahan. This examination utilizes subjective graphic exploration with a contextual investigation type. The subjects in this examination were school administrators and educators. Information assortment methods in this examination utilized perception, meetings and archive study. Information examination procedures incorporate information decrease, information show and making determinations. In the interim, testing the legitimacy of the information utilizes triangulation procedures. The aftereffects of the examination show that: (1) The Central’s administration in further developing educator execution at SDN 1 Penengahan is very great in creating instructor execution, observing educator execution, giving inspiration and assessing educator execution. In the mean time, educator execution is likewise very great in getting ready learning plans, overseeing learning exercises, and leading learning assessments. (2) The supporting element is solid help and inspiration from the school head. The restraining factors are the absence of LCD projectors and web organizations, the educator’s absence of capacity to deal with the class and utilize different learning techniques and the absence of instructor discipline. In view of the examination results, it is suggested that school chiefs make upgrades and assertions to educators so the vital’s administration cycle in further developing educator execution can then be done ideally..